Clinical pharmacokinetics and pharmacodynamics of ongericimab: A potential long‐acting PCSK9 monoclonal antibody in healthy subjects and patients with hypercholesterolemia: Randomized, double‐blind, placebo‐controlled phase Ia and Ib/II studies - Juanjuan Jiang; Li Xu; Lin Chai; Xiaoyuan Guan; Li Zhang; Hong Liu; Yan Yan; Lili Li; Yi Zhao; Xuelian Bai; Lei Tian; Youhong Jia (Wiley, 2024)
Abstract Proprotein convertase subtilisin/kexin type 9 (PCSK9) increases plasma low‐density lipoprotein‐cholesterol (LDL‐C) by decreasing the expression of the LDL‐receptor on hepatic cells. Ongericimab (JS002) is a novel PCSK9 monoclonal antibody that exhibits a long‐acting LDL‐C lowering effect by exclusively inhibiting PCSK9 in pre‐clinical studies. Two randomized, double‐blind, placebo‐controlled trials were conducted to evaluate the safety, tolerability, efficacy, immunogenicity, pharmacokinetic, and pharmacodynamic profiles of ongericimab in healthy subjects and patients with hypercholesterolemia. Eighty‐four healthy subjects in the phase Ia study received a single dose of placebo or ongericimab (15-450 mg). Ninety patients with hypercholesterolemia in the phase Ib/II study received placebo or ongericimab 150 mg Q2W, 300 mg Q4W, or 450 mg Q4W for 12 weeks. Ongericimab exhibited non‐linear kinetics. The apparent clearance decreased as the dosage increased, with terminal elimination half‐life (t1/2) values of 4.5-6.5 days. Overall, ongericimab was well tolerated in both studies. A single dose of ongericimab reduced LDL‐C levels by 30%-73% in healthy subjects, and repeated doses of ongericimab reduced LDL‐C levels by 67%-80% in patients with hypercholesterolemia. At the end of the dosing interval in the phase Ib/II study, over 70% of patients' LDL‐C levels decreased by more than 50% from baseline. The results showed that ongericimab had a significant long‐acting LDL‐C lowering effect with good safety and potential for clinical application.